Risk factors for dystocia in primiparous and pluriparous beef cows at the Besuki Animal Health Center, Situbondo Regency, East Java, Indonesia - Nisaaturrohma Fajriyah; Soeharsono Soeharsono; Oky Setyo Widodo (Ovozoa: Journal of Animal Reproduction, 2023)
This study aims to determine the risk factors for dystocia in primiparous and pluriparous dams at the study site. Cases of dystocia, both maternal and fetal, were obtained as secondary data from records at the Situbondo Regency Animal Husbandry Service for year 2020 and 2021. Tracking on these secondary data was carried out to look for cows experienced dystocia and the owners' names and addresses for interviews using a questionnaire worksheet. Interviews were conducted in February - May 2022 to obtain data on the maternal breed, age, feeding, fetal sex, and exercise frequency during pregnancy of the cows. Dystocia in the working area of the Besuki Animal Health Center in Sitobondo Regency in 2020 and 2021 occured in 50 cows which included primiparous (26%) and pluriparous (74%) cows. Breed, age, feed, and sex of the calves were not significantly different (p >0.05) between primiparous and pluriparous dams. However, the frequency of the exercises differed significantly (p <0.05) between primiparous and pluriparous dams. It could be concluded that the dystocia of cows in the study area was dominated by pluriparous parturition with exercises factor as the main cause.